Analyzing factors behind the successful adoption of the Samsat Digital National (SIGNAL) application for motor vehicle tax payment - Prabowo, Ilham Condro; Ramadhia, Muhammad Alifian (WIM Solusi Prima, 2024)
Officially launched by the Indonesian National Police in early 2023, the Samsat Digital Nasional (SIGNAL) application is a digital platform for motor vehicle tax payments, allowing taxpayers to pay via smartphones. This research aims to identify critical factors influencing the successful adoption of the SIGNAL application, such as perceived ease of use, perceived usefulness, enjoyment, and intention to use on actual use of the application, particularly in South Tangerang, Banten, Indonesia, using the Extended Technology Acceptance Model (TAM). Primary data for this study were collected through a questionnaire distributed to 98 respondents. It was found that 91 respondents met the criteria for taxpayers who had made tax payments using the SIGNAL application. The Data analysis method uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to explore the relationships between the variables. The results indicate that perceived ease of use and enjoyment positively influence users' intention to use, while perceived usefulness does not significantly affect intention to use. However, the intention to use positively significantly affects actual usage. These findings underscore the factors driving e-government service adoption and highlight the importance of user experience in application design. The study contributes to understanding digital service adoption in the public sector, suggesting that future strategies of Indonesian National Police should prioritize ease of use and enjoyment to enhance application usage.